Study the Effect of Cold Plasma on the Nonlinear Properties of Polymeric Membranes Rod Amine (R3Go) (Baghdad Science Journal, 2019)
The nonlinear optical properties for polymeric (PMMA) doping with dye Rhodmine (R3Go) has been studied .The samples are prepared by normal polymerization method with concentrations of 5x10-5mol/l and a thickness of 272.5µm. Plasma effect was studied on samples prepared before and after exposure to the Nd: YAG laser for three times 5, 10 and 15 minutes. Z-Scan technique is used to determine the nonlinear optical properties such as; refractive index (n2) and the coefficient of nonlinear absorption (β). It was found that the nonlinear properties is change by increasing of plasma exposure time, this result gives good indication about the effect of plasma on the internal structure of the polymer.